Architecture and health : guiding principles for practice - Wilhelm, Jacob J.; Battisto, Dina (New York : Routledge, 2020)
"Architecture and Health brings together architects, academics, social scientists and more to explore and analyse innovative design strategies that advance health. This book proposes a set of principles that can be used to design environments to promote health and healing, regardless of program or scale. Health and architecture are increasingly overlapping for designers in the 21st Century, with mounting evidence revealing that built environments are critical for people's health and well-being in everyday life. Architecture and Health focuses on principles related to architecture for health and well-being with a deep drive into specific case studies. Representing the United States, Africa, Asia, Europe, and Australia, each author brings a new perspective to health and its related architectural response. Eastern and Western philosophies and approaches to healthcare delivery demonstrate the power of design in promoting the health of individuals, communities, and our global ecology. This collection of award-winning projects such as hospitals, clinics, cancer centres, retail storefronts, gardens, and more provide alternative ways to achieve healing architecture. Architecture and Health brings a timely focus to a subject matter commonly constricted by normative building practices and transforms the dialogue into one of creativity and innovation"--
OCLC-licensed vendor bibliographic record.
Keywords: Architecture -- Health aspects; Health facilities -- Design and construction; Hospital buildings -- Design and construction; Environmental health; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting; ARCHITECTURE / Methods & Materials